Penerapan Balanced Scorecard pada Pengukuran Kinerja Trans Sarbagita - Wiguna, Eggy Prasutha; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2017)
Urban area as a business center and population density higher than rural, of course require facilities and infrastructure more complete transportation. One example of a region with high population density is Bali. Overcoming the disruption of mobility of urban and rural communities due to the congestion that occurs, it needs the development of mass transportation. One of them is the operation of Trans Sarbagita in Bali. Looking at the phenomenon above it is necessary to use a performance measurement model that can accommodate the need to view and assess the Trans Sarbagita comprehensively, namely by using the Balanced Scorecard. The purpose of this study is to describe the performance benchmarks and analyze from the perspective of Balanced Scorecard that is financial perspective, customer perspective, internal business perspective, persperktif growth and learning in accordance with the determination of vision, mission and objectives Trans Sarbagita. The population of this study is all passengers using Trans Sarbagita services and all UPT Trans Sarbagita employees who will be used for assessment on customer perspective, internal business process, and growth and learning. This research takes samples with Slovin formula with 90 samples of customers and 42 Sarbagita employees. Data were collected through interviews, documentation, and questionnaires. Data analysis technique in this research use descriptive analysis. The result of the research with Balanced Scorecard shows financial perspective, customer perspective, internal business perspective, growth perspective and learning get good result.